2004
DOI: 10.1046/j.1365-2982.2003.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the primary spinal afferent innervation of the mouse colon using retrograde labelling

Abstract: Visceral pain is the most common form of pain produced by disease and is thus of interest in the study of gastrointestinal (GI) complaints such as irritable bowel syndrome, in which sensory signals perceived as GI pain travel in extrinsic afferent neurones with cell bodies in the dorsal root ganglia (DRG). The DRG from which the primary spinal afferent innervation of the mouse descending colon arises are not well defined. This study has combined retrograde labelling and immunohistochemistry to identify and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
167
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(203 citation statements)
references
References 50 publications
30
167
6
Order By: Relevance
“…As expected and in agreement with existing literature (Jancso and Maggi 1987;Robinson et al 2004;Wang et al 1998;Zhong et al 2003), most bladder afferents projected from the L6-S1 DRG in both rodents, while a smaller, but still notable, population was present in TL DRG. In our studies, the distribution of retrogradelylabeled distal colon afferents also paralleled that of the bladder and, in general, was in agreement with the bimodal LS and TL peaks as noted in the Wistar rat (Vizzard et al 2000) and C57Bl/6 mice (Christianson et al 2006b;Robinson et al 2004). In support of the specificity of our labeling studies, dually-labeled cells were identified only at DRG levels that have previously been shown to contain both distal colon and urinary bladder afferents (Christianson et al 2006b;de Groat et al 1987;Keast and De Groat 1992;Robinson et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected and in agreement with existing literature (Jancso and Maggi 1987;Robinson et al 2004;Wang et al 1998;Zhong et al 2003), most bladder afferents projected from the L6-S1 DRG in both rodents, while a smaller, but still notable, population was present in TL DRG. In our studies, the distribution of retrogradelylabeled distal colon afferents also paralleled that of the bladder and, in general, was in agreement with the bimodal LS and TL peaks as noted in the Wistar rat (Vizzard et al 2000) and C57Bl/6 mice (Christianson et al 2006b;Robinson et al 2004). In support of the specificity of our labeling studies, dually-labeled cells were identified only at DRG levels that have previously been shown to contain both distal colon and urinary bladder afferents (Christianson et al 2006b;de Groat et al 1987;Keast and De Groat 1992;Robinson et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…In our studies, the distribution of retrogradelylabeled distal colon afferents also paralleled that of the bladder and, in general, was in agreement with the bimodal LS and TL peaks as noted in the Wistar rat (Vizzard et al 2000) and C57Bl/6 mice (Christianson et al 2006b;Robinson et al 2004). In support of the specificity of our labeling studies, dually-labeled cells were identified only at DRG levels that have previously been shown to contain both distal colon and urinary bladder afferents (Christianson et al 2006b;de Groat et al 1987;Keast and De Groat 1992;Robinson et al 2004). Further supporting the specificity of our findings, bladder denervation substantially reduced labeling of bladder afferents and consequentially the number of dually-labeled cells.…”
Section: Discussionsupporting
confidence: 89%
“…Dorsal Root Ganglia (DRG) from L6-S1 corresponds to the spinal level for the pelvic innervation of the colo-rectum (Hughes et al, 2007;Robinson et al, 2004). We found that L6-S1 DRG express MOR mRNA (Figure 3Bi), and this expression is substantially increased in L6-S1 DRG from CVH mice when compared to healthy mice (figure 3Bii).…”
Section: Pbmc Supernatants Inhibit Muscular / Mucosal Afferents In CVmentioning
confidence: 91%
“…It is abundant in peptidergic thoracolumbar vascular afferents, 113,114 and is detectable in the majority of their perivascular, intramuscular, ganglionic and mucosal axons in the gut wall. 115 TrpV1 might be directly activated by the acidosis that accompanies frank tissue damage 116 or by local increases in temperature during inflammation.…”
Section: Trp Channels In Vascular Afferentsmentioning
confidence: 99%